A Self-Dislodged Giant Tonsillolith: A case report and literature review - Yaroko, A.A. , Gobir, M.S. , Kirfi, A.M. (Sokoto Journal of Medical Laboratory Science)
Tonsillolith, otherwise known as calculi of the tonsil is the deposition of calcium crystals in the crypts of the palatine tonsil. Dysphagia, odynophagia and referred otalgia are the characteristic features of large calcification whereas smaller ones are usually asymptomatic. We present a 35 years old male security officer with 2 years history of throat pain with right sided otalgia and 2 days history of self-dislodged stone from the right tonsil.